Pitx3 deficiency promotes age-dependent alterations in striatal medium spiny neurons - Chen, Xi; Yang, Zhaofei; Shao, Yaping; Kim, Kunhyok; Wang, Yuanyuan; Wang, Ying; Wu, Haifeng; Xu, Xiaolan; Le, Weidong (Frontiers in Aging Neuroscience, 2022)
Background: The classical motor symptoms of Parkinson’s disease (PD) are tightly linked to the gradual loss of dopamine within the striatum. Concomitantly, striatal spiny projection neurons (SPNs) also experience morphological changes, such as reduced dendritic complexity and spine density, which may be potentially associated with motor dysfunction as well. Thus, SPNs may serve as the emerging targets for PD therapy besides the midbrain dopaminergic neurons. Results: To comprehensively examine pathological alterations of SPNs longitudinally, we established a THCre/Pitx3fl/ fl (Pitx3cKO) mouse model that developed canonical PD features, including a significant loss of SNc DAergic neurons and motor deficits. During aging, the targeted neurotransmitter, SPNs morphology and DNA methylation profile were significantly altered upon Pitx3 deficiency. Specifically, dopamine, GABA and glutamate decreased in the model at the early stage. While nuclear, soma and dendritic atrophy, as well as nuclear invaginations increased in the aged SPNs of Pitx3cko mice. Furthermore, more nuclear DNA damages were characterized in SPNs during aging, and Pitx3 deficiency aggravated this phenomenon, together with alterations of DNA methylation profiling associated with lipoprotein and nucleus pathway at the late stage. Conclusions: the early perturbations of the neurotransmitters within SPNs may potentially contribute to the alterations of metabolism, morphology and epigenetics within the striatum at the late stage, which may provide new perspectives on the diagnosis and pathogenesis of PD.